Faktor yang Berhubungan Dengan Unmet Need Kontrasepsi di Kalimantan Barat (Analisis Data SDKI 2017) - sohibun (Jurnal Ilmiah Cerebral Medika, 2021)
Background of Study: Unmet need for contraception is women who wish to space pregnancies or limit births but do not use contraception. The trend in the number of unmet need in West Kalimantan tends to be stagnant from 2012 and 2017 at 9.8, while the total fertility rate (TFR) is still high at 3.1. This case can become an obstacle in controlling population growth. This study aims to determine the factors associated with unmet need for contraception in West Kalimantan. Methods: The study used 2017 IDHS data with a cross sectional design, the population of women of reproductive age 15-49 years with a sample size of 876 respondents. The analysis used was chi-square and simple logistic regression. Results: the proportion of unmet need for contraception was 8.8 percent, the variables related to contraceptive unmet need were the number of living children with 1-2 children (p value = 0.0001), > 2 children (p value=0.0001), age 25-29 years (p value = 0.034), age 30-34 years (p value = 0.002), age 35-39 years (p value = 0.004), age 40-44 years (p value = 0.0001), age 45-49 years (p value = 0.0001), and the variable history of use of contraception p value = 0.0001. Conclusion: Variables related to unmet need for contraception are number of living children, age, and history of contraceptive use. Keywords: